A specific ortho-hydroxyl asymmetric column pentaarene functionalized gold nano composite photoelectric material glassy carbon electrode and a preparation method and application thereof
Patent Information
- Application Number
- CN202311239892.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-09-25
AI Technical Summary
Existing detection technologies suffer from low sensitivity, limited detection range, expensive instruments, require specialized operators, are inefficient, slow, and difficult to operate, making it difficult to achieve rapid, simple, and specific monitoring of intracellular reactive oxygen species levels.
A glassy carbon electrode of gold nanocomposite optoelectronic material functionalized with specific ortho-hydroxyl asymmetric columnar pentaaryl aromatic hydrocarbons was prepared by combining ortho-hydroxyl columnar pentaaryl aromatic hydrocarbons AP5 with gold nanoparticles to form a core-shell structure Au@AP5 composite optoelectronic material, which was then subjected to photoelectrochemical detection under visible light.
It enables rapid, simple, and specific monitoring of intracellular reactive oxygen species levels, with a wide detection range, high sensitivity, good reproducibility, and applicability to detection under different pH conditions. It also features a low detection limit and high recovery rate.
Smart Images

Figure CN117665068B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photoelectrochemical technology, specifically relating to a glassy carbon electrode of a specific ortho-hydroxyl-asymmetric columnar pentaaryl aromatic hydrocarbon functionalized gold nanocomposite photoelectric material, its preparation method, and its application. Background Technology
[0002] Reactive oxygen species (ROS) are highly unstable molecules that originate from endogenous sources (such as oxygen metabolism in the body) or exogenous sources (such as ionizing radiation). During oxygen metabolism in the body, complete oxygen reduction occurs in the mitochondria, involving a series of redox reactions controlled by complex enzymatic mechanisms. This reaction produces free radicals and non-free radical ROS, including hydrogen peroxide (H₂O₂), hydroxyl radicals (•OH), and peroxynitrite (ONOOH / ONOO). - ), singlet oxygen ( 1 O2), hypochlorous acid (HOCl / ClO-) and superoxide anion (O2) •- •OH (hydroxyl radicals) are important signaling factors in various cellular processes, maintaining the redox balance of cell proliferation and differentiation. •OH is highly reactive and can damage biomolecules such as carbohydrates, nucleic acids, lipids, and amino acids, posing a significant danger to organisms and humans. Therefore, developing detection technologies for rapid analysis of •OH is crucial.
[0003] Currently, various methods have been developed for the detection of •OH, including electrochemical methods, fluorescence methods, and electron spin resonance (ESR). Compared with these traditional methods, photoelectrochemical sensors have attracted increasing attention from researchers in recent years due to their advantages such as simple instrumentation, real-time system detection, high sensitivity and selectivity, fast response speed, small size, and convenient operation. The rapid development of nanotechnology and nanoscience has promoted the emergence of many new and innovative methods for the fabrication of nanomaterials for electrochemical ROS sensors. Various noble metal nanomaterials (Au, Ag, Pd, Pt) with good stability, high conductivity, high catalytic efficiency, low cytotoxicity, and ease of preparation and modification are widely used in photoelectrochemical sensors. However, the specific recognition of Au-based sensors is often limited due to the lack of specific functional groups. Therefore, coupling Au NPs with organic molecules with easily functionalized and specific functional groups is an effective way to achieve specificity.
[0004] In recent years, supramolecular structures such as stable ligands and functionalized metal nanomaterials have shown superior performance and potential application prospects in molecular recognition, sensing, and catalysis. As a new generation of macrocyclic host compounds, columnar aromatics have unique cavities, excellent host-guest complexing ability, and are easy to functionalize compared with the previous four generations. Columnar aromatics with different groups can be dissolved in polar and non-polar or even aqueous solutions. Therefore, columnar aromatics have the advantages of the previous four generations of macrocyclic supramolecular structures, as well as advantages that other supramolecular structures do not have. Specially functionalized columnar aromatics can be combined with other inorganic nanomaterials to give full play to the advantages of both, while also making up for the shortcomings of both. It has been reported that macrocyclic molecules combined with stable Au NPs combine the advantages of supramolecular structures and metal nanoparticles, and have unique photoelectrochemical properties. Therefore, a specific photoelectrochemical sensor system for recognizing •OH was designed, with ortho-hydroxy columnar aromatics[5] as the specific recognition molecule and gold nanoparticles as the photoactive material. Specific groups on AP5 react with •OH, and the resulting oxides can be oxidized and reduced on the electrode. In addition, the local surface plasmon resonance of Au NPs and the host-guest interaction between AP5 and •OH increase the photocurrent signal.
[0005] Therefore, the established Au@AP5 composite optoelectronic material sensor will open up a completely new way to monitor intracellular reactive oxygen species levels. It is fast, simple, and reproducible, and this sensor is expected to be used for online and on-site analysis in the future. Summary of the Invention
[0006] Technical problem solved: This application addresses the shortcomings of existing technologies by solving the technical problems of low sensitivity, limited detection range, expensive instruments, need for specialized operators, low efficiency, slow speed, and difficulty in operation of the original detection technology. It provides a glassy carbon electrode of a specific ortho-hydroxyl asymmetric columnar pentaaryl aromatic hydrocarbon functionalized gold nanocomposite optoelectronic material, its preparation method, and its application.
[0007] To achieve the above objectives, this application provides the following technical solution: A method for preparing a glassy carbon electrode of a specific ortho-hydroxyl-asymmetric columnar pentaaryl aromatic hydrocarbon-functionalized gold nanocomposite optoelectronic material, specifically including the following steps: The first step is to prepare the o-hydroxy columnar pentaary aromatic hydrocarbon AP5, which has a specific recognition group of •OH: ; The second step is to prepare Au nanoparticles: using chloroauric acid as a raw material and citric acid and sodium citrate as reducing agents, a spherical gold nanoparticle solution is prepared by thermal reduction. The ratio of chloroauric acid, citric acid and sodium citrate is 1-1.3 mL of 25.4 mM chloroauric acid : 0.9-1.2 mL of 0.1 M citric acid : 2.1-2.8 mL of 0.1 M sodium citrate. Step 3: Disperse 0.8 ~ 1.2 mg AP5 in 0.3 ~ 0.7 mL of spherical gold nanoparticle solution using ultrasonic method according to dosage ratio. Utilize the thiol-SH on AP5 to bond with Au to synthesize core-shell structured specific ortho-hydroxyl asymmetric columnar pentaaryl aromatic hydrocarbon functionalized gold nanocomposite optoelectronic material, namely Au@AP5 composite optoelectronic material. Step 4: On a surface area of 0.07 cm² 2 A glassy carbon electrode with a specific ortho-hydroxyl asymmetric columnar pentaaryl aromatic hydrocarbon functionalized gold nanocomposite optoelectronic material, namely Au@AP5 / GCE electrode, was prepared by drop-coating 10 μL of Au@AP5 composite optoelectronic material solution onto the glassy carbon electrode.
[0008] Furthermore, the first step specifically includes the following steps: Step a: Dissolve 10-15 g of 90.8-136.2 mmol hydroquinone, 5.10-7.62 g of 90.9-136.0 mmol potassium hydroxide, and 7.8-11.7 mL of 90.5-135.8 mmol 1,2-dibromoethane in 200 mL of methanol solution. Stir under reflux at 70-75 °C for 16-19 h. After filtering out inorganic salts, evaporate the solvent and purify the residue by silica gel column chromatography to obtain 13-16 g of white solid powder as compound A, with a yield of 15-17%. Step b: Add 40.0–48.4 mmol of compound A (8.7–10.5 g), 48.0–58.0 mmol of methyl chloroacetate (5.2–6.3 g), and 60.0–72.6 mmol of anhydrous potassium carbonate (8.3–10.0 g) to 250 mL of acetonitrile solution. Stir the mixture at 80–85 °C for 12–15 h. After removing inorganic salts by filtration, evaporate the solvent and wash the condensate residue with anhydrous ethanol. 10.6–12.3 g of white solid, compound B, is obtained, with a yield of 82–86%. Step c: Dissolve 20.0–24.9 mmol of compound B (5.8–7.2 g), 80.0–99.6 mmol of hydroquinone dimethyl (11.0–13.7 g), and 30–37.4 mmol of paraformaldehyde (3.0–3.7 g) in 20–30 mL of dichloromethane; add 23.0–28.6 mmol of boron trifluoride diethyl ether (3.0–3.6 g) to the solution, stir at 400 rpm for 2 h at room temperature, wash the reaction mixture with water, and dry with anhydrous sodium sulfate; evaporate the solvent to obtain the crude product, which is purified by column chromatography to obtain 1.5–2.3 g of white solid as compound C, with a yield of 8–10%. Step d: Dissolve 1 ~ 1.5 mmol of compound C 0.89 ~ 1.3 g and 2.0 ~ 3.0 mmol of thiourea 0.15 ~ 0.2 g in 8 ~ 10 mL of DMF, heat overnight at 80 ~ 85 °C under nitrogen protection, cool to room temperature, add 20 ~ 23 mL of 1M NaOH aqueous solution and continue stirring for 1 ~ 1.3 h, then acidify with HCl to pH 3; extract three times with diethyl ether combined with organic phase, wash with brine, dry with anhydrous sodium sulfate; remove solvent by rotary evaporation, purify the residue by silica gel flash column chromatography, and obtain 0.63 ~ 0.78 g of white solid powder, namely column [5] aromatic D, with a yield of 75 ~ 77%; Step e: Add 0.25 ~ 0.4 mmol column[5] aromatic D 0.2 ~ 0.3 g and 0.2 ~ 0.4 mmol 2-aminophenol 0.027 ~ 0.05 g to dichloromethane, add 0.4 ~ 0.8 mmol 1-hydroxybenzotriazole 0.054 ~ 0.09 g and 0.4 ~ 0.8 mmol 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride 0.077 ~ 0.14 g, and stir in a water bath at 40 ~ 45 °C for 22 ~ 24 h; evaporate the solvent and purify by column chromatography to obtain 0.061 ~ 0.074 g of white solid powder, namely o-hydroxy column pentaaryl aromatic AP5, with a yield of 24 ~ 26%.
[0009] Further, the specific steps for preparing spherical gold nanoparticles in the second step are as follows: 0.9 ~ 1.2 mL of citric acid and 2.1 ~ 2.8 mL of sodium citrate are added to 150 ~ 200 mL of boiling water by volume ratio and stirred for 15 min; then 1 ~ 1.3 mL of chloroauric acid is added, and after stirring for 3 min, the mixture is cooled in ice water. The precipitate obtained above is washed with ultrapure water and ethanol, and the precipitate is dispersed in ultrapure water to obtain a dispersion of spherical gold nanoparticles.
[0010] Furthermore, the ultrasonic time in the third step is 1 hour.
[0011] This application also discloses a glassy carbon electrode of a specific ortho-hydroxyl-asymmetric columnar pentaaryl aromatic hydrocarbon functionalized gold nanocomposite optoelectronic material prepared by the above preparation method.
[0012] An application of a glassy carbon electrode made of a specific ortho-hydroxyl-asymmetric columnar pentaaryl aromatic hydrocarbon-functionalized gold nanocomposite material in the photoelectric detection of •OH in cells was described. A traditional three-electrode system was used, with an Au@AP5 / GCE electrode as the working electrode, a platinum mesh as the counter electrode, and a saturated calomel electrode (SCE) as the reference electrode. The surface of the Au@AP5 / GCE electrode was irradiated with a xenon lamp simulating a visible light source, and the shading interval was controlled as an adjustable "on-off" state. Photoelectric detection was then performed using an electrochemical workstation in a •OH solution.
[0013] The working principle of the aforementioned Au@AP5 composite optoelectronic material is as follows: Under visible light irradiation, Au nanoparticles, which have good conductivity, strong light absorption capacity, and LSPR effect, generate electron-hole pairs. The positively charged holes oxidize •OH in the solution, accelerating electron transfer and increasing photocurrent. AP5 has host-guest complexing ability, which can adsorb •OH, and the specific groups on AP5 react with •OH to increase photocurrent, thereby achieving specific and real-time monitoring of •OH in cells.
[0014] This application provides a glassy carbon electrode of a specific ortho-hydroxyl-asymmetric columnar pentaaryl aromatic hydrocarbon-functionalized gold nanocomposite optoelectronic material, its preparation method, and its application. Compared with the prior art, it has the following advantages: 1. This application designs Au nanoparticles that form under visible light with LSPR effect, and AP5 with host-guest complexation ability and reaction with •OH, for photoelectrochemical detection of •OH in cells; 2. To solve the technical problems of existing detection technologies, such as low sensitivity, limited detection range, serious environmental pollution, expensive instruments, need for specialized operators, low efficiency, slow speed, and difficulty in operation; 3. The detection range of this application is divided into two parts: one is the detection range of 1 μM ~ 250 μM when the maximum photocurrent response is at pH=2; the other is the detection range of 0.3 μM ~ 100 mM when •OH in the human body is detected in real time at pH=7.4, with detection limits of 0.33 μM and 0.1 μM (S / N = 3), respectively. 4. The recovery rate of •OH in human serum detected by this application was 97.20%-100.30% at pH=2 and 99.1%-98.3% at pH=7.4; 5. The detection of •OH in this application has good reproducibility, with relative standard deviations of 1.8% for 5 parallel experiments and 1.5% for pH=7. Attached Figure Description
[0015] Figure 1 The Au nanoparticles (a) and Au@AP5 in this application (b) Transmission electron micrograph; Figure 2 The XRD powder diffraction patterns (A) of AP5 and Au@AP5 in this application, the UV-Vis absorption spectra (B) of Au, AP5 and Au@AP5 and the FT-IR spectra (C) of Au, AP5 and Au@AP5; Figure 3 The images show EIS characterization (A) of Au, AP5, and Au@AP5 in 1 mM K3[Fe(CN)6] / K4[Fe(CN)6] + 0.1 M KCl solution and DPVs (B) of Au, AP5, and Au@AP5 electrodes under illumination in 10 μM •OH + 0.1 M PBS solution (pH = 7.4). Figure 4 The DPVs and CVs (A, C) and calibration curves (B, D) of Au@AP5 in different concentrations of •OH + 0.1 M PBS solutions (pH = 2 and 7.4) in this application are shown. Figure 5 This is a flowchart of the synthesis method of AP5 in this application. Detailed Implementation
[0016] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and equivalent alterations or modifications also fall within the scope defined by the claims of this application.
[0017] Example 1: A method for preparing a glassy carbon electrode of a specific ortho-hydroxyl-asymmetric columnar pentaaryl aromatic hydrocarbon functionalized gold nanocomposite optoelectronic material. The specific ortho-hydroxyl-asymmetric columnar pentaaryl aromatic hydrocarbon functionalized gold nanocomposite optoelectronic material is an Au@AP5 composite optoelectronic material prepared by ultrasonically bonding a novel asymmetric columnar pentaaryl aromatic hydrocarbon onto the surface of Au nanoparticles. The specific steps include the following: Step 1: Preparation of o-hydroxy-columnar pentaaryl aromatic hydrocarbon AP5 with a •OH specific recognition group: 90.8 mmol hydroquinone (10 g), 90.9 mmol potassium hydroxide (5.10 g), and 90.5 mmol 1,2-dibromoethane (7.8 mL) were dissolved in 200 mL of methanol solution. The mixture was stirred under reflux at 70 °C for 16 h. After filtering to remove inorganic salts, the solvent was evaporated, and the residue was purified by silica gel column chromatography to obtain 13 g of white solid powder, compound A (yield 15%). 40.0 mmol compound A (8.7 g), 48.0 mmol methyl chloroacetate (5.2 g), and 60.0 mmol anhydrous potassium carbonate (8.3 g) were added to 250 mL of acetonitrile solution. The mixture was stirred at 80 °C for 12 h. After filtering to remove inorganic salts, the solvent was evaporated, and the condensate residue was washed with anhydrous ethanol to obtain 9.5 g of white solid, compound B (yield 82%). 20.0 mmol compound B (5.8 g) was then added to the methanol solution. 80.0 mmol hydroquinone dimethyl 11.0 g and 30 mmol trioxymethylene 3.0 g were dissolved in 20 mL of dichloromethane; 23.0 mmol boron trifluoride diethyl ether 3.0 g was added to the solution, and the mixture was stirred at 400 rpm for 2 h at room temperature. The reaction mixture was washed with water and dried with anhydrous sodium sulfate. The solvent was evaporated to obtain the crude product, and 1.5 g of white solid was obtained by column chromatography, which was compound C, with a yield of 8%. 1 mmol of compound C 0.89 g and 2.0 mmol of thiourea 0.15 g were dissolved in 8 mL of DMF, heated at 80 °C overnight under nitrogen protection, cooled to room temperature, and 20 mL of 1M NaOH aqueous solution was added and stirred for 1 h. Then, the solution was acidified with 1M HCl to pH 3. The organic phase was extracted three times with diethyl ether, washed with brine, and dried with anhydrous sodium sulfate. The solvent was removed by rotary evaporation, and the residue was purified by silica gel flash column chromatography to obtain 0.63 g of white solid powder, i.e. column [5] aromatic D, Yield 75%; 0.25 mmol column[5] aromatic D 0.21 g and 0.25 mmol 2-aminophenol 0.027 g were added to dichloromethane, followed by 0.4 mmol 1-hydroxybenzotriazole 0.054 g and 0.40 mmol 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride 0.077 g. The mixture was stirred in a water bath at 40℃ for 22 h. The solvent was evaporated and purified by column chromatography to obtain 0.061 g of white solid powder, namely o-hydroxy column pentaaryl aromatic AP5, with a yield of 25%;
[0018] The second step is to prepare Au nanoparticles: 0.9 mL of citric acid and 2.1 mL of sodium citrate are added to 150 mL of boiling water and stirred for 15 min; then 1 mL of chloroauric acid is added and stirred for 3 min. After cooling in ice water, the precipitate obtained above is washed with ultrapure water and ethanol. The precipitate is dispersed in 4 mL of ultrapure water to obtain a dispersion of spherical gold nanoparticles. Step 3: 0.8 mg AP5 was dispersed in 0.3 mL of spherical gold nanoparticle solution by ultrasonication. The core-shell structure of specific ortho-hydroxyl asymmetric columnar pentaaryl aromatic hydrocarbon functionalized gold nanocomposite optoelectronic material, namely Au@AP5 composite optoelectronic material, was synthesized by utilizing the thiol-SH bond on AP5 with Au. Step 4: On a surface area of 0.07 cm² 2 A glassy carbon electrode with a specific ortho-hydroxyl asymmetric columnar pentaaryl aromatic hydrocarbon functionalized gold nanocomposite optoelectronic material, namely Au@AP5 / GCE electrode, was prepared by drop-coating 10 μL of Au@AP5 composite optoelectronic material solution onto the glassy carbon electrode.
[0019] Example 2: Application of a glassy carbon electrode made of a specific ortho-hydroxyl-asymmetric columnar pentaaryl aromatic hydrocarbon-functionalized gold nanocomposite in the photoelectric detection of •OH in cells. The Au@AP5 / GCE electrode was placed in a •OH solution for photoelectrochemical detection. All experiments used a conventional three-electrode system, with the Au@AP5 / GCE electrode as the working electrode, a platinum mesh as the counter electrode, and a saturated calomel electrode (SCE) as the reference electrode. A xenon lamp was used to simulate a visible light source to irradiate the surface of the Au@AP5 / GCE electrode, and the shading interval was controlled as an adjustable "on-off" state. Photoelectrochemical detection was then performed using an electrochemical workstation.
[0020] Performance testing: 1. Morphology determination of Au nanoparticles and Au@AP5 composite optoelectronic materials: from Figure 1 As can be seen from A, the diameter of the prepared Au nanoparticles is approximately 20 nm. From... Figure 1 As can be seen from B, the original morphology and size of Au nanoparticles remain basically unchanged after AP5 functionalization.
[0021] 2. XRD powder diffraction, UV characterization and FT-IR spectroscopy of Au nanoparticles and Au@AP5 composite optoelectronic materials Figure 2Figure A shows the XRD powder diffraction patterns of Au and Au@AP5. The diffraction peaks of Au@AP5 correspond to the typical XRD peaks of Au NPs at 38.19°, 44.39°, 64.58°, 77.57°, and 81.72°, respectively, distributed on the Au (111), (200), (311), and (222) crystal planes (Au, JCPDS number: 89-3697). The typical amorphous diffraction peaks of Au@AP5 at 18.11° and 22.90° should be superimposed diffraction peaks of AP5.
[0022] Figure 2 B represents the UV-Vis absorption spectra of Au, AP5, and Au@AP5. The typical UV-Vis peak of Au NPs is located at 521 nm, which is consistent with previous reports. Column [5] Aromatics have obvious absorption peaks at 250 ~ 350 nm. Therefore, the characteristic absorption peaks of Au@AP5 at 527 nm and 250 ~ 350 nm prove that Au NPs and AP5 exist and are conjugated in the sample, and the red shift of the Au NP absorption peak indicates that AP5 was successfully introduced into the surface of Au NPs.
[0023] Figure 2 C represents the infrared spectral characterization of AP5 and Au@AP5. As can be seen from the figure, the infrared spectra at 742-879, 927, 1040-1280, 1648, 2827, and 2930 cm⁻¹ are... -1 Typical stretching vibration peaks were observed at 3850 cm⁻¹, confirming the presence of CH, OH, CO, NH, -OCH₃, and -CH₂-. Furthermore, the FT-IR spectrum of AP₅ showed peaks at 3850 cm⁻¹. -1 There are tensile vibration peaks on the left and right, but they almost disappear in the FT-IR spectrum of Au@AP5, indicating that the -SH of AP5 disappears or weakens when it is connected to the Au NPs surface.
[0024] 3. Electrochemical characterization: like Figure 3 As shown in Figure A, impedance spectroscopy (EIS) measurements were performed in 5.0 mM K3[Fe(CN)6] / K4[Fe(CN)6] and 0.1 M KCl solutions. The calculated Rct values for Au, AP5, and Au@AP5 were 732.1 Ω, 13980 Ω, and 25930 Ω, respectively. Au exhibits the lowest charge transfer resistance. When AP5 is introduced onto Au, the Rct value of the Au@AP5 electrode decreases significantly, which is attributed to the non-conductive nature of AP5. Figure 3 As shown in Figure B, the effects of Au / GCE, AP5 / GCE, and Au@AP5 / GCE electrodes on visible light irradiation in the presence of 10 μM •OH were investigated using differential pulse voltammetry. Photoelectrochemical activity in +0.1 M PBS (pH=7.4) solution. Compared with Au / GCE and AP5 / GCE, the oxidation photocurrent density on Au@AP5 / GCE is significantly increased. This is mainly due to the redox reaction of the oxidation products of AP5 on the electrode, and the photogenerated electron-hole pairs generated by Au NPs under visible light will increase the photocurrent response.
[0025] 4. Electrochemical detection of •OH: like Figure 4 As shown in Figure A, when pH=2, the photocurrent density of the sensor increases linearly with the increase of •OH concentration from 1 μM to 250 μM. Its linear regression equation is ( Figure 4 In equation B), I(µA) = 9.2943 lg(c) + 19.8157, and the correlation coefficient RB is given. 2 = 0.9948. For example... Figure 4 As shown in Figure C, at pH = 7.4, the photocurrent density of the sensor increases linearly with the •OH concentration increasing from 0.3 μM to 100 mM. Compared to pH = 2, it has a larger detection range, but the detection accuracy is relatively lower. Its linear regression equation is ( Figure 4 The correlation coefficient R is given by I(µA) = 5.5593 lg(c) + 2.3816. 2 = 0.9948. Therefore, the calculated LOD is 0.1 μM (S / N = 3), which is lower than other detection methods, indicating that the Au@AP5 photoelectrochemical sensor has superior analytical performance.
[0026] Example 3: A method for preparing a glassy carbon electrode of a gold nanocomposite optoelectronic material with specific o-hydroxyl asymmetric columnar pentaaryl aromatic hydrocarbons, specifically including the following steps: Step 1: Preparation of o-hydroxyl columnar pentaaryl aromatic hydrocarbon AP5 with a specific •OH recognition group: 15 g of 136.2 mmol hydroquinone, 7.62 g of 136.0 mmol potassium hydroxide, and 11.7 mL of 135.8 mmol 1,2-dibromoethane were dissolved in 200 mL of methanol solution and stirred under reflux at 75 °C for 19 h. After filtering out inorganic salts, the solvent was evaporated, and the residue was purified by silica gel column chromatography to obtain 16 g of white solid powder as compound A, with a yield of 17%; 10.5 g of 48.4 mmol compound A, 6.3 g of 58.0 mmol methyl chloroacetate, and 10.0 g of 72.6 mmol anhydrous potassium carbonate were added to 250 mL of acetonitrile solution, and the mixture was stirred at 85 °C for 15 h. After removing inorganic salts by filtration, the solvent was evaporated, and the condensate residue was washed with anhydrous ethanol to obtain 12.3 g of white solid as compound B, with a yield of 86%. 24.9 mmol of compound B (7.2 g), 99.6 mmol of hydroquinone dimethyl (13.7 g), and 37.4 mmol of paraformaldehyde (3.7 g) were dissolved in 30 mL of dichloromethane. 28.6 mmol of boron trifluoride diethyl ether (3.6 g) was added to the solution, and the mixture was stirred at 400 rpm for 2 h at room temperature. The reaction mixture was washed with water and dried over anhydrous sodium sulfate. The solvent was evaporated to obtain the crude product, which was purified by column chromatography to obtain 2.3 g of white solid as compound C, with a yield of 10%. 1.5 mmol of compound C (1.3 g) and 3.0 mmol of thiourea (0.2 g) were dissolved in 10 mL of DMF, heated overnight at 85°C under nitrogen protection, cooled to room temperature, and 23 mL of 1M NaOH aqueous solution was added. The mixture was stirred for 1.3 h, and then dissolved in 1M HCl. Acidified to pH 3; extracted three times with organic phase diethyl ether, washed with brine, and dried with anhydrous sodium sulfate; the solvent was removed by rotary evaporation, and the residue was purified by silica gel flash column chromatography to obtain 0.78 g of white solid powder, namely column[5]arene D, with a yield of 77%; 0.3 g of column[5]arene D and 0.05 g of 2-aminophenol were added to dichloromethane, and 0.09 g of 1-hydroxybenzotriazole and 0.14 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride were added. The mixture was stirred in a water bath at 45°C for 24 h; the solvent was evaporated, and the mixture was purified by column chromatography to obtain 0.074 g of white solid powder, namely o-hydroxy column pentaaryl aromatic hydrocarbon AP5, with a yield of 26%;
[0027] The second step is to prepare Au nanoparticles: 1.2 mL of citric acid and 2.8 mL of sodium citrate are added to 200 mL of boiling water and stirred for 15 min; then 1.3 mL of chloroauric acid is added and stirred for 3 min. The mixture is then cooled in ice water, and the precipitate obtained above is washed with ultrapure water and ethanol. The precipitate is then dispersed in an ultrapure water solution to obtain a dispersion of spherical gold nanoparticles. Step 3: 1.2 mg AP5 was dispersed in 0.7 mL of spherical gold nanoparticle solution by ultrasonication. The core-shell structure of specific ortho-hydroxyl asymmetric columnar pentaaryl aromatic hydrocarbon functionalized gold nanocomposite optoelectronic material, namely Au@AP5 composite optoelectronic material, was synthesized by using the thiol-SH on AP5 to bond with Au. Step 4: On a surface area of 0.07 cm² 2 A glassy carbon electrode with a specific ortho-hydroxyl asymmetric columnar pentaaryl aromatic hydrocarbon functionalized gold nanocomposite optoelectronic material, namely Au@AP5 / GCE electrode, was prepared by drop-coating 10 μL of Au@AP5 composite optoelectronic material solution onto the glassy carbon electrode.
[0028] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.
Claims
1. A method for preparing a glassy carbon electrode of a specific ortho-hydroxyl-asymmetric columnar pentaaryl aromatic hydrocarbon-functionalized gold nanocomposite optoelectronic material, characterized in that, Specifically, the steps include: The first step is to prepare the o-hydroxy columnar pentaary aromatic hydrocarbon AP5, which has a specific recognition group of •OH: ; The second step is to prepare Au nanoparticles: using chloroauric acid as a raw material and citric acid and sodium citrate as reducing agents, a spherical gold nanoparticle solution is prepared by thermal reduction. The ratio of chloroauric acid, citric acid and sodium citrate is 1-1.3 mL of 25.4 mM chloroauric acid : 0.9-1.2 mL of 0.1 M citric acid : 2.1-2.8 mL of 0.1 M sodium citrate. Step 3: Disperse 0.8-1.2 mg AP5 in 0.3-0.7 mL of spherical gold nanoparticle solution using an ultrasonic method according to the dosage ratio. Utilize the thiol-SH group on AP5 to bond with Au to synthesize a core-shell structured, specific ortho-hydroxyl asymmetric columnar pentaaryl aromatic hydrocarbon functionalized gold nanocomposite optoelectronic material, namely Au@AP5 composite optoelectronic material. Step 4: On a surface area of 0.07 cm² 2 A glassy carbon electrode with a specific ortho-hydroxyl asymmetric columnar pentaaryl aromatic hydrocarbon functionalized gold nanocomposite optoelectronic material, namely Au@AP5 / GCE electrode, was prepared by drop-coating 10 μL of Au@AP5 composite optoelectronic material solution onto the glassy carbon electrode.
2. The method for preparing a glassy carbon electrode of a specific ortho-hydroxyl-asymmetric columnar pentaaryl aromatic hydrocarbon functionalized gold nanocomposite optoelectronic material according to claim 1, characterized in that, The first step specifically includes the following steps: Step a: Dissolve 10-15 g of 90.8-136.2 mmol hydroquinone, 5.10-7.62 g of 90.9-136.0 mmol potassium hydroxide, and 7.8-11.7 mL of 90.5-135.8 mmol 1,2-dibromoethane in 200 mL of methanol solution. Stir at reflux at 70-75 °C for 16-19 h. After filtering out inorganic salts, evaporate the solvent and purify the residue by silica gel column chromatography to obtain 13-16 g of white solid powder as compound A, with a yield of 15-17%. Step b: Add 40.0–48.4 mmol of compound A (8.7–10.5 g), 48.0–58.0 mmol of methyl chloroacetate (5.2–6.3 g), and 60.0–72.6 mmol of anhydrous potassium carbonate (8.3–10.0 g) to 250 mL of acetonitrile solution. Stir the mixture at 80–85 °C for 12–15 h. After removing inorganic salts by filtration, evaporate the solvent and wash the condensate residue with anhydrous ethanol. 10.6–12.3 g of white solid, compound B, is obtained, with a yield of 82–86%. Step c: Dissolve 20.0–24.9 mmol of compound B (5.8–7.2 g), 80.0–99.6 mmol of hydroquinone dimethyl (11.0–13.7 g), and 30–37.4 mmol of paraformaldehyde (3.0–3.7 g) in 20–30 mL of dichloromethane; add 23.0–28.6 mmol of boron trifluoride diethyl ether (3.0–3.6 g) to the solution, stir at 400 rpm for 2 h at room temperature, wash the reaction mixture with water, and dry with anhydrous sodium sulfate; evaporate the solvent to obtain the crude product, which is purified by column chromatography to obtain 1.5–2.3 g of white solid as compound C, with a yield of 8–10%. Step d: Dissolve 1 ~ 1.5 mmol of compound C 0.89 ~ 1.3 g and 2.0 ~ 3.0 mmol of thiourea 0.15 ~ 0.2 g in 8 ~ 10 mL of DMF, heat overnight at 80 ~ 85 °C under nitrogen protection, cool to room temperature, add 20 ~ 23 mL of 1M NaOH aqueous solution and continue stirring for 1 ~ 1.3 h, then acidify with 1M HCl to pH 3; extract three times with diethyl ether combined with organic phase, wash with brine, dry with anhydrous sodium sulfate; remove solvent by rotary evaporation, purify the residue by silica gel flash column chromatography, and obtain 0.63 ~ 0.78 g of white solid powder, namely column [5] aromatic D, with a yield of 75 ~ 77%; Step e: Add 0.25 ~ 0.4 mmol of columnar aromatic hydrocarbon D [5] 0.25 ~ 0.3 g and 0.2 ~ 0.4 mmol of 2-aminophenol 0.027 ~ 0.05 g to dichloromethane, add 0.4 ~ 0.8 mmol of 1-hydroxybenzotriazole 0.054 ~ 0.09 g and 0.4 ~ 0.8 mmol of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride 0.077 ~ 0.14 g, and stir in a water bath at 40 ~ 45 °C for 22 ~ 24 h; evaporate the solvent and purify by column chromatography to obtain 0.061 ~ 0.074 g of white solid powder, namely o-hydroxy columnar pentaaryl aromatic hydrocarbon AP5, with a yield of 24 ~ 26%.
3. The method for preparing a glassy carbon electrode of a specific ortho-hydroxyl-asymmetric columnar pentaaryl aromatic hydrocarbon functionalized gold nanocomposite optoelectronic material according to claim 1, characterized in that, The second step of preparing spherical gold nanoparticles is as follows: 0.9-1.2 mL of citric acid and 2.1-2.8 mL of sodium citrate are added to 150-200 mL of boiling water by volume and stirred for 15 min; then 1-1.3 mL of chloroauric acid is added and stirred for 3 min. After cooling in ice water, the precipitate is washed with ultrapure water and ethanol and dispersed in 4 mL of ultrapure water to obtain a dispersion of spherical gold nanoparticles.
4. The method for preparing a glassy carbon electrode of a specific ortho-hydroxyl-asymmetric columnar pentaaryl aromatic hydrocarbon functionalized gold nanocomposite optoelectronic material according to claim 1, characterized in that: The ultrasonic time in the third step is 1 hour.
5. A glassy carbon electrode of a specific ortho-hydroxyl-asymmetric columnar pentaaryl aromatic hydrocarbon-functionalized gold nanocomposite optoelectronic material prepared by any of the preparation methods of claims 1-4.
6. The application of the glassy carbon electrode of the specific ortho-hydroxyl-asymmetric columnar pentaaryl aromatic hydrocarbon-functionalized gold nanocomposite photoelectric material according to claim 5 in the photoelectric detection of •OH in cells, characterized in that: Using a traditional three-electrode system, with the Au@AP5 / GCE electrode as the working electrode, a platinum mesh as the counter electrode, and a saturated calomel electrode (SCE) as the reference electrode, the surface of the Au@AP5 / GCE electrode was irradiated with a xenon lamp simulating a visible light source. The shading interval was controlled as an adjustable "on-off" process, and photoelectrochemical detection was performed using an electrochemical workstation in •OH solution.
